Community Pharmacist-Provided Osteoporosis Screening and Education: Impact on Patient Knowledge - Andrea L. Brookhart; K. Michelle Brown Fountain; Leticia R. Moczygemba; Jean-Venable R. Goode (University of Minnesota Libraries Publishing, 2015)
Objective: To evaluate the impact pharmacist-provided screening and education had on patient knowledge of osteoporosis and preventive strategies. Methods: A prospective, randomized, controlled study was conducted at 16 locations of a national supermarket chain pharmacy in the Richmond, Virginia area. Women 30 years and older with no history of osteoporosis were enrolled in the study. Patients self-selected into the study by agreeing to the bone density screening, pharmacist-provided education, and completion of a knowledge survey. Subjects were randomized to complete the osteoporosis-related knowledge survey either before (Group A) or after (Group B) the screening and education session. The survey was developed after guideline and literature evaluation and was pretested with a group of patients for content and clarity. The survey evaluated knowledge of osteoporosis, risk factors for the disease, appropriate age for testing, and preventive strategies. Groups A and B were compared using t-tests. Results: A total of 110 women were enrolled in the study. The mean (±SD) age was 52.5 ± 13.1 years in Group A (n=52) and 52.7 ± 11.5 years in Group B (n=58). Knowledge scores were higher in the group who received pharmacist-provided education prior to completing the survey in each category (knowledge of the disease, risk factors, preventive strategies, and appropriate age for testing) and overall (p<0.001). Conclusions: Community pharmacist-provided osteoporosis screening and education increased patient knowledge about osteoporosis and preventive strategies. Community pharmacist involvement with increasing patient knowledge may empower patients to engage in prevention strategies to improve bone mass.   Type: Original Research